Analisis Dasar Pertimbangan Hakim Dalam Penjatuhan Pidana Terhadap Pelaku Tindak Pidana Penyelundupan Satwa Liar (Studi Putusan Nomor 305/Pid.Sus-LH/2025/PN Kla) - Yohanes Putra Parlindungan Sormin; Rinaldy Amrullah; Tri Andrisman (Journal of Education Religion Humanities and Multidiciplinary, 2026)
Criminal acts are acts that often occur in the general public, the factor of a person committing an act or criminal act can be caused by many things, one of which is an economic factor where a person can do any act to be able to meet the needs of his life, one of which is by committing criminal acts that are prohibited by law. One of these criminal acts is smuggling, especially wildlife. The area of Indonesia itself has a diversity of flora and fauna which causes Indonesia to have a very wide distribution of animals. This is used by individuals to capture and smuggle the animals to gain benefits in the form of wages. Therefore, this study will discuss Decision Number 305/Pid.Sus-LH/2025/PN Kla where the Defendant Sabar bin Saradi committed a criminal act in the form of smuggling that had a negative impact on the population of endemic birds and on the balance of natural ecosystems. The number of wildlife to be smuggled reached a total of 1,008 (one thousand eight) heads with the aim of going to Java Island, more precisely to Serang, Banten. This study aims to examine the basis of the judge's consideration in deciding this smuggling case both from the aspects of juridical, sociological and philosophical considerations. For this research method, a normative approach is used that focuses on secondary data analysis in the form of primary legal materials, namely laws, secondary legal materials in the form of books, journals, and legal scientific works and tertiary legal materials in the form of dictionaries and legal encyclopedias. According to his consideration, the consideration of the Panel of Judges has qualified as a consideration based on justice because the Panel of Judges has examined all aspects such as juridical, sociological, and philosophical so that a final result of the verdict was obtained by stating that the defendant was guilty of committing a criminal act in the form of transporting protected wildlife in a state of life and was subject to imprisonment for 1 year. however, the Panel of Judges did not add the imposition of a fine on the Defendant considering that the economic ability possessed by the Defendant was unable to pay if a fine of Rp. 50,000,000.00 (fifty million rupiah) was imposed.